Network Pharmacology and Molecular Docking to Unveil the Mechanism of Shudihuang against Amyotrophic Lateral Sclerosis - Li, Xiaojing; Tian, Yueqin; Wu, Haidong; Wang, Tong (Current pharmaceutical design, 2023)
Shudihuang has been clinically proven to be an effective Chinese medicine compatible with the treatment of amyotrophic lateral sclerosis. However, the underlying mechanism of Shudihuang against amyotrophic lateral sclerosis remains unclear. The present study aims to elucidate the possible mechanism of Shudihuang in treating ALS using network pharmacology and molecular docking. The primary active components of Shudihuang and their relevant targets were identified by the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and the Swiss Target Prediction database, respectively. The ALS-related targets were obtained from the Disgenet and OMIM databases. The shared targets were derived by the intersection of disease-associated and component-associated targets and then introduced into the Cytoscape software to construct a network of drug-component-target. In addition, protein interaction relationships among the shared targets were analyzed by the STRING and Cytoscape software. Furthermore, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) functional enrichment analysis were conducted by the Metascape platform. The binding activities between the hub targets and the active components were assessed with molecular docking. Stigmasterol and sitosterol were identified as the core components of Shudihuang, and the hub targets of ALS are PTGS2, PPARG, ESR1, IGF-1R, and MAPK3, with the highest degrees in the PPI network. The finding that stigmasterol and sitosterol had a good affinity with PTGS2, PPARG, ESR1, IGF-1R, and MAPK3 also supported this. Finally, it was revealed that Shudihuang treatment of ALS predominantly involves estrogen- related pathways such as nuclear receptor activity and steroid binding. In summary, this study suggested that the main active components of Shudihuang (stigmasterol and sitosterol) may exert a critical effect in ALS treatment by binding to hub targets (PTGS2, PPARG, ESR1, IGF-1R, and MAPK3) and then modulating estrogen receptor-related pathways to attenuate glutamate excitotoxicity, inhibit oxidative stress and antagonize inflammation.